Enhancement of Muscle T Regulatory Cells and Improvement of Muscular Dystrophic Process in mdx Mice by Blockade of Extracellular ATP/P2X Axis - Gazzerro, Elisabetta; Baldassari, Simona; Assereto, Stefania; Fruscione, Floriana; Pistorio, Angela; Panicucci, Chiara; Volpi, Stefano; Perruzza, Lisa; Fiorillo, Chiara; Minetti, Carlo; Traggiai, Elisabetta; Grassi, Fabio; et al. (The American journal of pathology, 2015)
Infiltration of immune cells and chronic inflammation substantially affect skeletal and cardiac muscle degeneration in Duchenne muscular dystrophy. In the immune system, extracellular adenosine triphosphate (ATP) released by dying cells is sensed as a danger associated molecular pattern through P2 purinergic receptors. Specifically, the P2X7 subtype has a prominent role in regulating immune system physiology and contributes to inflammasome activation also in muscle cells. Here, we show that in vivo blockade of the extracellular ATP/P2X purinergic signaling pathway by periodate-oxidized ATP delayed the progression of the dystrophic phenotype and dampened the local inflammatory response in mdx mice, a spontaneous mouse model of dystrophin deficiency. Reduced infiltration of leukocytes and macrophages and decreased expression of IL-6 were revealed in the muscles of periodate-oxidized ATP-treated mdx mice. Concomitantly, an increase in Foxp3+ immunosuppressive regulatory T cells was observed and correlated with enhanced myofiber regeneration. Moreover, we detected reduced concentrations of profibrotic cytokines, including transforming growth factor-β and connective tissue growth factor, in muscles of periodate-oxidized ATP-treated mdx mice. The improvement of inflammatory features was associated with increased strength and reduced necrosis, thus suggesting that pharmacologic purinergic antagonism altering the adaptive immune component in the muscle infiltrates might represent a promising therapeutic approach in Duchenne muscular dystrophy.